KINERJA KOPERASI PERIKANAN GOTONG ROYONG DESA KUOK KECAMATAN BANGKINANG BARAT KABUPATEN KAMPAR PROVINSI RIAU - Zulkarnaini '; Jon Budi Prayogo (Berkala Perikanan Terubuk, 2013)
The research was conducted from June 30 th to July 31 st 2013 in Kuokvillage, Bangkinang Barat district, Kampar sub province, Riau province.Thepurpose of this research was to knowing the performance of Gotong Royongfisheries cooperation Kuok village Kampar sub province. This research usedsurvey method. From the research result known that result of calculations basedon the Ministry of Cooperatives and Small and Medium Enterprises show that theperformance of the fisheries cooperation is sufficient quality.Keywords : Performance, Fisheries Cooperation, Kuok Village.